Welcoming new neighbors: Minnesota's rapid response model to address the urgent health needs of Afghan newcomers, 2021–2022 - Frumholtz, Mateo; Carlson, William C.; Shannon, Patricia J.; Iaquinta, Sophia; Eckerstorfer, Maggie; Hendel-Paterson, Brett; Quadri, Nasreen; Shetty, Rashika; Mohammadzadah, Hadia; Stauffer, William; Adesida, Opeyemi; Howard, Cindy; et al. (Frontiers in Public Health, 2024)
As a result of the United States withdrawal from Afghanistan in fall 2021, 1,260 Afghan evacuees arrived in Minnesota between October 2021 and February 2022. Several contextual factors including an overtaxed health system under duress from COVID-19 and uncertain benefit eligibility prompted a coordinated public health response to appropriately address the acute and pressing medical concerns of our new neighbors. This community case study describes the State of Minnesota’s cross-sectoral response that created a welcoming environment, identified public health concerns, and addressed acute medical needs. Medical volunteers provided an initial health and safety check for Afghan families upon arrival. Volunteers also offered onsite culturally and linguistically appropriate mental health assessments, group therapy, women’s clinics, vaccine clinics, medication refills, and ongoing walk-in primary care. Care coordinators facilitated primary care and specialty care referrals. The majority (96%) of eligible arrivals were screened as part of this response and the median time between arrival to Minnesota and initial health screening was two days. Half of all arrivals screened reported at least one health concern and 56% were referred to a specialty for further evaluation. Almost one in four adults (24%) reported mental health concerns. Existing partnerships across local sectors can be leveraged to provide comprehensive physical and mental health services to newcomers in an emergency response.